Carbon-coated nano-silicon negative electrode material with doped elements distributed dispersedly and preparation method of carbon-coated nano-silicon negative electrode material
By using a carbon-coated nanosilicon structure with a diffuse distribution of doped elements in the lithium-ion battery negative electrode material, the problems of volume change and conductivity of the silicon negative electrode material are solved, and the battery performance with high capacity and good cycle stability is achieved.
Patent Information
- Application Number
- CN202411616886.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-03-18
AI Technical Summary
Silicon-based lithium-ion battery anode materials have poor performance in operating life, Coulomb efficiency, rate performance and other key indicators, mainly due to the loss of crushing and electrical contact caused by volume changes in silicon during lithium alloying, as well as the problems of low conductivity and low lithium ion diffusion rates.
The carbon-coated nano-silicon anode material with a dispersion distribution of doped elements is used to coat the nano-silicon with a doping element, such as boron, and form a carbon cladding layer on the surface of the nano-silicon, to suppress the volume expansion of silicon, and improve conductivity and cycling performance.
It achieves ultra-high capacity and good cycle stability, improves the comprehensive mechanical properties and electrochemical properties of the negative electrode materials, and extends the cycle life of the battery.
Smart Images

Figure CN119650617A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of negative electrode materials for lithium ion batteries, and in particular relates to a carbon-coated nano-silicon negative electrode material with dispersed distribution of doping elements and a preparation method thereof. Background Art
[0002] As global attention to energy issues intensifies, advanced energy storage technologies play a vital role in our daily lives. As a representative of these technologies, lithium-ion batteries (LIBs) have been widely studied in the past few decades. Taking graphite anode as an example, commercial LIBs have approached their theoretical specific capacity limit (372 mAh g -1 ). However, with the increasing popularity of electric vehicles and portable electronic devices, the demand for LIBs with higher specific energy density continues to grow. Researchers are now focusing on finding negative electrode materials with higher theoretical specific capacity, and silicon (Si) stands out as a strong competitor to replace graphite in the next generation of LIBs. Si has high abundance, huge theoretical specific capacity (3579mAh g -1 ) and suitable working potential (<0.5V vs. Li + / Li).
[0003] However, Si-based anodes face significant challenges. First, during lithium alloying, Si undergoes a significant volume change (about 300%), resulting in pulverization of active materials and loss of electrical contact. Second, the diffusion rate of lithium ions in Si electrodes is low, resulting in a significant lithium ion concentration gradient and incomplete lithium extraction during cycling. In addition, the low electrical conductivity of Si (2.52×10 -6 S cm -1 ) makes the broken fragments insulated and unable to participate in subsequent charge and discharge cycles. Eventually, the fresh surface generated by the pulverization directly contacts the electrolyte, resulting in a large consumption of the solid electrolyte interface (SEI) film, which reduces the coulombic efficiency of the battery. These shortcomings together lead to the poor performance of Si-based anodes in LIBs in terms of working life, coulombic efficiency, rate performance and other key indicators.
[0004] To address the above challenges, nanointervention has emerged as an effective strategy to alleviate the internal stress caused by the volume expansion of silicon, which is one of the conditions for maintaining the normal operation of silicon anodes. To address these issues, various nanoscale structures have been studied, including nanoparticles, nanotubes, nanowires, two-dimensional films, and porous structures. Although nanoscale silicon (nSi) has demonstrated extended battery cycle life in laboratory environments, it has brought new obstacles to industrial applications. For example, the reduced tap density of nSi significantly reduces the volumetric energy density of LIBs, and its large specific surface area leads to serious side reactions, affecting the Coulombic efficiency. In addition, the complex processing of nanomaterials increases the manufacturing cost. Recognizing the gap between laboratory research and industrial deployment, researchers are now turning their attention to submicron silicon (μSi) in anode research. Compared with nSi, μSi has a larger tap density, smaller specific surface area, and lower synthesis cost, making it more promising for industrial applications. Recent efforts in μSi research have focused on alleviating the volume expansion problem during cycling and improving conductivity, resulting in significant progress in μSi anode LIBs. Timely and comprehensive summary and analysis of this field is essential to promote the development and industrial application of silicon-based anodes in LIBs. Summary of the invention
[0005] Based on solving the technical problems existing in the background technology, the present invention proposes a carbon-coated nano-silicon negative electrode material with dispersed distribution of doped elements and its preparation. The nano-silicon negative electrode material suppresses the volume expansion of silicon through element doping and carbon coating, and obtains ultra-high capacity and good cycle stability.
[0006] The present invention provides a carbon-coated nano-silicon negative electrode material with dispersed doping elements, comprising doped nano-silicon and a carbon coating layer coated on the surface of the doped nano-silicon;
[0007] In the doped nano-silicon, the doping elements are dispersed inside the nano-silicon.
[0008] In the present invention, in order to solve the problem of poor electrical conductivity of silicon when storing lithium, on the one hand, the excellent electrical conductivity of carbon is utilized to form a carbon coating layer on the surface of silicon, which not only suppresses the volume expansion of silicon, but also improves the cycle performance and rate performance of the nano-silicon negative electrode material; on the other hand, the doping elements are dispersed and distributed inside the nano-silicon to achieve the dispersion strengthening function of the nano-silicon negative electrode material, which fully improves the comprehensive mechanical properties of the silicon negative electrode material, avoids the pulverization and breakage of the silicon negative electrode material due to stress concentration, and thus improves its cycle life.
[0009] Preferably, the doping element is boron, and its particle size is 3-5 nm.
[0010] Preferably, the particle size of the nano-silicon negative electrode material is 100-300 nm.
[0011] The present invention also provides a method for preparing a carbon-coated nano-silicon negative electrode material with dispersed distribution of doping elements, comprising the following steps:
[0012] S1, mixing silicon oxide, doping element oxide, chloride salt and reducing agent, performing thermal reduction reaction, and acid washing to obtain doped nano-silicon;
[0013] S2. Mixing the doped nano-silicon and the organic carbon source and carbonizing them at high temperature to obtain the nano-silicon negative electrode material.
[0014] In the present invention, nano silicon oxide and a mixture of doped element oxides are used as raw materials. After reduction by a metal reducing agent, the generation of porous nano silicon and the trace dispersion doping of the corresponding element of the doping element can be completed simultaneously. Thereafter, an amorphous carbon layer is formed by carbonization by an organic carbon source and tightly coated on the surface of the nano silicon. On the one hand, the corresponding element of the doping element is distributed in the nano silicon in a dispersed phase, which can improve the diffusion kinetics of lithium ions in solid silicon, reduce electrode polarization, and alleviate the volume effect, thereby helping to improve the specific capacity, rate performance and cycle stability of the silicon material. On the other hand, the amorphous carbon layer tightly coats the porous nano silicon, providing effective support for the shrinkage and expansion of the porous nano silicon particles during the lithium insertion and extraction process, inhibiting the pulverization of the porous silicon particles, thereby improving the cycle stability of the electrode. In general, the present invention can make full use of the high capacity of silicon-based materials to improve the capacity and cycle rate performance of negative electrode materials. Its specific structure can not only effectively alleviate the volume expansion of silicon-based materials during charging and discharging, but also shorten the lithium ion diffusion path and increase the liquid absorption performance of the material through the porous structure of the material to improve the electrochemical performance of the material.
[0015] Preferably, in step S1, the doping element is boron and the oxide is boron oxide;
[0016] In the present invention, the particle size of the doping element oxide is preferably ≤0.5 mm, and the metal reducing agent is preferably a powder of 200 mesh or finer.
[0017] Preferably, the molar ratio of silicon to doping element in the silicon oxide and the doping element oxide is 100-x:x, 1≤x≤2.
[0018] In the present invention, by strictly controlling the doping amount of the doping element, the content of the inactive phase in the obtained nano-silicon negative electrode material can be reduced, and its electrochemical performance is effectively optimized; if the doping element can also store lithium, it can cooperate with the silicon element to jointly improve the performance and significantly improve the reversible capacity.
[0019] Preferably, in step S1, the chloride salt is at least one of lithium chloride, sodium chloride, potassium chloride, rubidium chloride or cesium chloride; the metal reducing agent is at least one of magnesium powder, aluminum powder or zinc powder;
[0020] Preferably, the weight ratio of the nano silicon oxide, the chloride salt and the metal reducing agent is 1:2-5:1.5-2.
[0021] In the present invention, the metal reducing agent is slightly excessive, preferably added at 105% of the theoretical calculated amount, to prevent the metal reducing agent from evaporating and causing insufficient metal reducing agent; the amount of chloride salt used is 2-5 times the total mass of the oxide. When the mass of the chloride salt is lower than this range, the specific structure of the nano-silicon negative electrode material of the present invention cannot be synthesized, and when it is higher than this range, the cost is increased;
[0022] Preferably, the reactor for the thermal reduction reaction is a stainless steel closed reactor to reduce the volatilization of the metal reducing agent.
[0023] Preferably, in step S1, the thermal reduction reaction temperature is 1450-1550°C, the time is 2-4h, and the heating rate is 10-30°C / min;
[0024] In the present invention, the reaction temperature is controlled to prevent particle agglomeration, and finally a carbon-coated nano-silicon negative electrode material with dispersed distribution of doping elements is obtained, and excellent electrochemical performance is obtained.
[0025] In the present invention, a too fast heating rate will damage the resistance wire of the furnace, and the faster the heating rate, the worse the accuracy of temperature control.
[0026] Preferably, the pickling uses at least one of hydrochloric acid, sulfuric acid, nitric acid or hydrofluoric acid, with a concentration of 1-10wt% and a pickling time of 3-6h.
[0027] In the present invention, the pickling method adopts ultrasonic pickling, and the solution used for ultrasonic pickling is a sufficient amount of hydrochloric acid solution or hydrofluoric acid solution that has been deoxygenated in advance.
[0028] Preferably, in step S2, the organic carbon source is dopamine.
[0029] In the present invention, the advantage of dopamine being polymerized on the surface of nano-silicon in an aqueous solution to form polydopamine is utilized to prepare a carbon-coated nano-silicon negative electrode material.
[0030] Preferably, the dopamine is chitosan-modified dopamine.
[0031] In the present invention, when chitosan-modified dopamine is used as an organic carbon source, in addition to being polymerized on the surface of nano-silicon, the steric hindrance and electrostatic repulsion generated by chitosan-modified dopamine can also improve the dispersibility of nano-silicon, which helps to obtain a carbon-coated nano-silicon negative electrode material with better electrochemical performance.
[0032] Preferably, in step S2, the high temperature carbonization temperature is 700-900°C and the time is 1-3h.
[0033] The present invention also provides a lithium-ion battery, which comprises the above-mentioned nano-silicon negative electrode material or the silicon negative electrode material prepared by the above-mentioned preparation method.
[0034] In the present invention, when the doping element is boron, in order to solve the problem of poor conductivity of silicon when storing lithium, the excellent conductivity of carbon is utilized, and by means of magnesium thermal reaction of additional addition of chloride molten salt, the construction of silicon nanostructure, the internal bulk phase dispersion doping of boron and the in-situ coating of carbon are completed at the same time, and the final product is obtained, that is, the carbon-coated nano-silicon negative electrode material with the doping element dispersedly distributed. The negative electrode material has excellent electrochemical lithium storage performance. Due to its unique surface coating of amorphous carbon, the direct contact between the active material and the electrolyte is directly isolated, and the structural stability and the first coulomb efficiency are improved; the nanostructure reduces the specific surface area of the negative electrode material, improves the first coulomb efficiency of the negative electrode material, the dispersed distribution of boron inside the silicon, and improves the structural stability of the negative electrode material, thereby improving the cycle performance of the negative electrode material; at the same time, because the boron inside the silicon is dispersedly distributed, it has the function of dispersion strengthening for the negative electrode material, fully improves the comprehensive mechanical properties of the negative electrode material, avoids the material pulverization and crushing caused by stress concentration, thereby improving its cycle life. In summary, the combination of three improvement methods, namely nanostructure, surface amorphous carbon layer coating, and internal boron diffuse doping, ultimately results in a negative electrode material that shows ultra-high capacity and excellent rate performance, and has high potential for commercial application.
[0035] Beneficial effects of the present invention:
[0036] (1) The present invention innovatively proposes a new synthesis method for carbon-coated nanoscale negative electrode materials, providing a reference scheme for the synthesis of in-situ carbon-coated negative electrode materials;
[0037] (2) The present invention can prepare carbon-coated nano-silicon negative electrode materials with dispersed doping elements on a large scale, with low cost, simple and easy method, large-scale production and high commercial value;
[0038] (3) The nano-scale silicon negative electrode material prepared by the present invention can realize rapid lithium ion extraction / embedding reaction, bring excellent lithium storage performance, and has good commercial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 is the phase diagram of B-Si alloy;
[0040] Figure 2 This is a SEM image of the nano-silicon negative electrode material described in Example 1 of the present invention;
[0041] Figure 3 This is a Raman spectrum of the nano-silicon negative electrode material described in Example 1 of the present invention. DETAILED DESCRIPTION
[0042] Example 1
[0043] This embodiment provides a carbon-coated nano-silicon negative electrode material with dispersed doping elements, and the specific steps of the preparation method are as follows:
[0044] (1) Place 1 g of silicon dioxide, 5.85 mg of boron oxide powder (particle size ≤ 0.5 mm), 1.3 g of sodium chloride, 1.3 g of potassium chloride and 1.55 g of magnesium powder (particle size ≤ 0.075 mm) in a mixer and mix for 1 h until fully mixed;
[0045] (2) placing the obtained mixed powder in a stainless steel reactor, heating it to 1500°C at a heating rate of 20°C / min in an argon atmosphere furnace, keeping it at that temperature for 3 hours, and then cooling it to room temperature in the furnace;
[0046] (3) adding the obtained product to hydrochloric acid (content of 6 wt%), ultrasonically pickling for 4 h, filtering, washing until neutral, and vacuum drying;
[0047] (4) adding the obtained dry powder into 500 mL of dopamine solution (Tris buffer adjusted to pH 8.5, concentration 2 g / L), stirring and mixing thoroughly, filtering and freeze-drying;
[0048] (5) The obtained freeze-dried powder is placed in a reaction kettle, heated to 800° C. in a hydrogen atmosphere furnace, and kept warm for 2 hours. After the reaction is completed, it is cooled to room temperature to obtain the nano-silicon negative electrode material.
[0049] Figure 1 is the B-Si alloy phase diagram, Figure 1 It can be seen that when the atomic ratio of silicon to boron is 99:1, boron cannot form an alloy with silicon. Therefore, the material is kept warm at 1500°C for 3 hours. At this time, the magnesium powder is liquid, the synthesized silicon is liquid, and the boron is solid. The diffusion process of the liquid phase is used to make the reaction uniform. During the long-term heat preservation process, boron gradually diffuses from the surface to the inside under the action of the chemical gradient, and is finally dispersed in the silicon phase to obtain the doped nano-silicon.
[0050] Figure 2 This is a SEM image of the nano-silicon negative electrode material described in Example 1 of the present invention. Figure 2 It can be seen that the final sample is spherical particles with a particle size between 100-300nm.
[0051] Figure 3 This is the Raman spectrum of the nano-silicon negative electrode material described in Example 1 of the present invention, Figure 3 It can be seen that the final sample contains carbon elements and has a high defect concentration, which can significantly improve the conductivity and ion conductivity of the sample. This nanoscale structure can realize rapid ion extraction / embedding reaction, bringing excellent lithium storage performance.
[0052] It can be seen from the above embodiments that the present invention can use magnesium powder, silicon oxide and boron oxide as raw materials, sodium chloride and potassium chloride as molten salts, and through magnesium thermal reaction, a carbon-coated nano-silicon negative electrode material doped with boron is dispersedly distributed, and the boron element is dispersedly distributed inside the nanoparticles; then, the carbon element is in situ doped by thermal decomposition and reduction of dopamine to generate a thin and uniform amorphous carbon layer coated on the surface of the skeleton; at the same time, the mixed salt has a low melting point, which provides a high-fluidity liquid phase environment for the reaction and promotes the nano-sizing of the material.
[0053] Example 2
[0054] This embodiment provides a carbon-coated nano-silicon negative electrode material with dispersed distribution of doping elements. The preparation method thereof is similar to that of Embodiment 1, except that in step (1), 11.82 mg of boron oxide powder (particle size ≤ 0.5 mm) is added.
[0055] Example 3
[0056] This embodiment provides a carbon-coated nano-silicon negative electrode material with dispersed distribution of doping elements. The preparation method thereof is similar to that of Embodiment 1, except that in step (2), the temperature is raised to 1550° C. and kept for 2 h, with a heating rate of 30° C. / min.
[0057] Example 4
[0058] This embodiment provides a carbon-coated nano-silicon negative electrode material with dispersed distribution of doping elements. The preparation method thereof is similar to that of Embodiment 1, except that in step (2), the temperature is raised to 1450° C. and kept for 4 hours at a heating rate of 10° C. / min.
[0059] Example 5
[0060] This embodiment provides a carbon-coated nano-silicon anode material with dispersed doping elements. The preparation method thereof is the same as that of Embodiment 1, except that in step (4), the dopamine solution is a chitosan-modified dopamine solution;
[0061] The chitosan-modified dopamine solution is prepared by the following method: 0.9 g dopamine is dissolved in 500 mL distilled water and mixed evenly, after the pH is adjusted to 8.5 with Tris buffer, 0.01 g 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 0.005 g N-hydroxysuccinimide and 0.1 g carboxymethyl chitosan are added, and the reaction is stirred for 12 hours to obtain the chitosan-modified dopamine solution.
[0062] Comparative Example 1
[0063] This comparative example proposes a carbon-coated nano-silicon negative electrode material, and its preparation method is similar to that of Example 1, except that in step (1), 17.92 mg of boron oxide powder (particle size ≤ 0.5 mm) is added.
[0064] Comparative Example 2
[0065] This comparative example proposes a carbon-coated nano-silicon negative electrode material, and its preparation method is referred to Example 1, except that in step (2), the temperature is raised to 1400°C.
[0066] Comparative Example 3
[0067] This comparative example proposes a carbon-coated nano-silicon negative electrode material, and its preparation method refers to Example 1, except that in step (1), the addition of 1.3 g of sodium chloride and 1.3 g of potassium chloride is omitted.
[0068] The nano-silicon negative electrode material described in the above embodiments and comparative examples is used as the negative electrode material, mixed with a conductive agent (Super-P) and a binder sodium carboxymethyl cellulose (CMC) in a mass ratio of 80:10:10, and an appropriate amount of ultrapure water is added to form a slurry, which is coated on a copper foil, and is vacuum dried and rolled to prepare a negative electrode sheet; the positive electrode uses a metallic lithium sheet, the electrolyte uses a solvent of 1 mol / L LiPF6 conductive salt and a ethylene carbonate / diethyl carbonate solution with 2% vinylene carbonate added, and the diaphragm uses a polypropylene microporous membrane. The above materials are assembled into a button battery.
[0069] The charge and discharge test of button cells was carried out on the Blue Power Battery Test System at room temperature with a constant current of 0.1C and a charge and discharge voltage limit of 0.005-1.5V. The results are shown in Table 1 below.
[0070] Table 1 shows the electrochemical properties of the nano-silicon negative electrode materials described in the examples and comparative examples.
[0071]
[0072]
[0073] It can be seen from Table 1 above that the nano-silicon negative electrode material of the present invention has high specific capacity, good cycle stability and good stability.
[0074] In Comparative Example 1, since the atomic ratio of silicon and boron is too small, the dispersion distribution of boron inside silicon is poor, and the electrochemical performance of the nano-silicon negative electrode material is reduced; in Comparative Example 2, the reaction temperature is 1400°C, which is lower than the melting point of silicon 1414°C. The boron in the nano-silicon negative electrode material cannot be dispersed inside the nano-silicon sphere, and the electrochemical performance is also reduced; in Comparative Example 3, no molten salt is added, and the obtained product cannot maintain a nano-spherical shape, but a three-dimensional skeleton structure, and the electrochemical performance is significantly reduced.
[0075] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A carbon-coated nano-silicon negative electrode material with dispersed distribution of doping elements, characterized in that: It includes doped nano-silicon and a carbon coating layer coated on the surface of the doped nano-silicon; In the doped nano-silicon, the doping elements are dispersed inside the nano-silicon.
2. The carbon-coated nano-silicon negative electrode material with dispersed doping phase according to claim 1, characterized in that: The doping element is boron, and its particle size is 3-5nm.
3. The carbon-coated nano-silicon negative electrode material with dispersed doping elements according to claim 1 or 2, characterized in that: The particle size of the nano-silicon negative electrode material is 100-300nm.
4. A method for preparing a carbon-coated nano-silicon negative electrode material with dispersed distribution of doping elements, characterized in that: The steps include: S1, mixing silicon oxide, doping element oxide, chloride salt and metal reducing agent, performing thermal reduction reaction, and acid washing to obtain doped nano-silicon; S2. Mixing the doped nano-silicon and the organic carbon source and carbonizing them at high temperature to obtain the nano-silicon negative electrode material.
5. The method for preparing the carbon-coated nano-silicon negative electrode material with dispersed distribution of doping elements according to claim 4, characterized in that: In step S1, the doping element is boron and the oxide is boron oxide; Preferably, the molar ratio of silicon to doping element in the silicon oxide and the doping element oxide is 100-x:x, 1≤x≤2.
6. The method for preparing the carbon-coated nano-silicon negative electrode material with dispersed distribution of doping elements according to claim 4 or 5, characterized in that: In step S1, the chloride salt is at least one of lithium chloride, sodium chloride, potassium chloride, rubidium chloride or cesium chloride; the metal reducing agent is at least one of magnesium powder, aluminum powder or zinc powder; Preferably, the weight ratio of the nano silicon oxide, the chloride salt and the metal reducing agent is 1:2-5:1.5-2.
7. The method for preparing the carbon-coated nano-silicon negative electrode material with dispersed distribution of doping elements according to any one of claims 4 to 6, characterized in that: In step S1, the thermal reduction reaction temperature is 1440-1550°C, the time is 2-4h, and the heating rate is 10-30°C / min; Preferably, the pickling uses at least one of hydrochloric acid, sulfuric acid, nitric acid or hydrofluoric acid, with a concentration of 1-10wt% and a pickling time of 3-6h.
8. The method for preparing the carbon-coated nano-silicon negative electrode material with dispersed distribution of doping elements according to any one of claims 4 to 7, characterized in that: In step S2, the organic carbon source is dopamine; Preferably, the dopamine is chitosan-modified dopamine.
9. The method for preparing the carbon-coated nano-silicon negative electrode material with dispersed distribution of doping elements according to any one of claims 4 to 8, characterized in that: In step S2, the high temperature carbonization temperature is 700-900°C and the time is 1-3h.
10. A lithium ion battery, characterized in that: It comprises the nano silicon negative electrode material according to any one of claims 1 to 3 or the silicon negative electrode material prepared by the preparation method according to any one of claims 4 to 9.